PH-sensitive doxorubicin-conjugated prodrug micelles with charge-conversion for cancer therapy. (1st April 2018) - Ma, Boxuan; Zhuang, Weihua; Wang, Yanan; Luo, Rifang; Wang, Yunbing
Graphical abstract: Abstract: Intelligent drug delivery systems with prolonged circulation time, reduced drug leakage in blood, target site-triggered drug release and endosomal escape are attractive and ideal for malignant tumor therapy. Herein, doxorubicin (DOX)-conjugated smart polymeric micelles based on 4-carboxy benzaldehyde-grafted poly (L-lysine)-block-poly (methacryloyloxyethyl phosphorylcholine) (PLL(CB/DOX)-b-PMPC) copolymer are prepared. DOX and electronegative 4-carboxy benzaldehyde are conjugated to the PLL block via an imine linkage and as a result, the drug loaded micelles exhibited the pH-triggered charge-conversion property and accelerated drug release at tumor pH. In vitro cytotoxicity studies of these DOX-loaded micelles exhibited great tumor inhibition against HeLa and 4T1 cells. Moreover, in mice models of breast cancer, these DOX-loaded micelles showed better anti-tumor efficacy and less organ toxicity than free drug. In summary, these polymeric micelles could be applied as potential nanocarriers for cancer therapy. Statement of Significance: As a typical anti-cancer drug, Doxorubicin (DOX) exhibited remarkable tumor inhibition but was limited by its low drug utilization and strong toxicity to organs. To overcome these challenges, we developed a DOX-conjugated polymeric micelle as a nano drug carrier which was endowed with pH-sensitivity and charge-conversion function. The structure of micelles would quickly disintegrate with surface charge-conversion in acidic environment, which would contribute to the endosomal escape and accelerated drug release. These DOX-conjugated micelles would provide a promising platform for the efficient DOX delivery and better anti-cancer efficiency.